E-067 Endovascular occlusion of a carotid cavernous arteriovenous fistula complicated with posterior communicating artery-sphenoparietal sinus fistula: a case report, technical consideration, and literature review. (22nd July 2019) - Mathkour, M; Berry, J; McCormack, E; Valle-Giler, E
Abstract : Background: Traumatic injury of the posterior communicating artery causing arteriovenous fistula is rare. Here, we present a complicated case in which a patient presented with a traumatic carotid-cavernous fistula and subsequently developed recurrence. Recurrence was complicated by shunting of the posterior communicating artery to the sphenoparietal sinus post-treatment that was successfully treated endovascularly. Method: A 53-year-old male with a remote history of head trauma complicated by posttraumatic right cavernous carotid fistula presented with progressive headaches. He was treated at another facility via trans-superior ophthalmic vein coil embolization several years prior.CT angiography demonstrated recurrence with a complex fistula. Further investigation via cerebral angiogram demonstrated a type A direct high flow cavernous-carotid fistula with cortical venous drainage and multiple venous aneurysms. Result: The fistula was treated by R ICA deconstruction with coil and Onyx embolization after a balloon occlusion test. Follow up MRI after one year suggested a continued low-pressure fistula. He subsequently underwent cerebral angiogram which showed an indirect fistula, with feeders from ethmoidal arteries and branches of the internal maxillary artery. Outflow was through the sphenoparietal sinus. There was a direct fistula communication in between the posterior communicating artery and fistula outflow. Via the R PCommA, the fistula outflow was embolized using coils and Onyx with almost complete obliteration of the fistula and minimal to no reflux into the right posterior communicating artery. The patient did well postoperatively with complete resolution of headaches and was seen recently in clinic for 6 months follow up visit. Conclusion: We present a patient with carotid-cavernous arteriovenous fistula complicated by subsequent fistula between the posterior communicating artery and sphenoparietal sinus successfully endovascularly treated with complete obliteration of the fistula without reflux. To our knowledge, this is the first such report. We present this case to review the multiple challenges of managing complicated traumatic carotid cavernous arteriovenous fistula and to highlight the utility of endovascular intervention in their treatment. Disclosures: M. Mathkour: None. J. Berry: None. E. McCormack: None. E. Valle-Giler: None.